Hubungan Orang Tua Menderita Miopia dengan Kejadian Miopia pada Anaknya di SDN Cemara 2 Surakarta - Narityastuti, Dwi Budi; Indrakila, Senyum; Setyawan, Sigit (Nexus Kedokteran Klinik, 2014)
Background: Myopia has become a serious problem in some countries all over the world, particularly in Asia. Most number of myopia cases found in elementary school children. Its etiology is complex and is likely to involve the interaction genetic influences. This study aims to determine the relationship of genetic factors with the incidence of myopia in primary school age children. Methods:This is an observational analytic study using cross sectional approach which was conducted on May - June 2013. Two hundred elementary students with myopia in Cemara 2 Surakarta Elementary School met the criteria of restriction after getting eyes examination. Genetic factor and near work activities was acquired from questionnaire. Near work activities divided into how. The data were analyzed by use of chi square and multiple logistic regression, on SPSS 17.0. Difference was established by Odds Ratio (OR), significance was indicated by p value. Result: Chi-Square test analysis showed a significant association between parents suffers from myopia with the incidence of myopia in children. The analysis of the results obtained p <0.05,with value of p = 0.004. While the results for near work activities showed no significant p> 0.005. Conclusion: There is a relationship between parents suffer myopia with incidence of myopia in children at Cemara 2 Surakarta Elementary School. There was no relationship between the working distance is close to myopia in children. Keywords: Myopia, Genetic, Parental Myopia, Elementary StudentsÂ